(untitled) (Research, Society and Development, 2020)
Faced with the Coronavirus pandemic scenario, which has been devastating the world since the end of 2019, there are still many uncertainties surrounding this disease, COVID-19, and the pediatric public, especially children with chronic diseases. Considering this reality, the objective of this article is to know about the scientific publications of COVID-19 in children with chronic diseases. It is a study of systematic review of the literature of the type Scoping Reviews. The search was carried out from May to August 2020 in the electronic databases Sci Verse Scopus, Latin-American and Caribbean Literature in Health Sciences, Public MEDLINE, Current Nursing and Allied Health Literature and Embase and totaled 5,570 scientific productions. The final sample consisted of 46 articles in full, whose contents were extracted by conceptual categories: susceptibility / risk factors; clinical manifestations; hospitalization; care strategies and preventive measures in relation to COVID-19 in children with chronic diseases. The research concludes that children with chronic diseases represent a group of the population that may be at an increased risk for complications from COVID-19. However, the studies analyzed show that there is no reason to suspend the treatment of children with chronic diseases during the pandemic and that it is essential to assess the risk versus the benefit of initiating or maintaining treatment in cases of children confirmed for COVID-19.